Peran Integrasi Keilmuan dalam Membentuk Keluarga Berbasis Nilai-Nilai Islam Studi Keluarga Qur’an Surah Al-Imran - Suchi Nurul Khofifah; Bintang Arif Samudra; Muhammad Nasrullah Ramadhana; Mohammad Alfarabi; Zaini Dahlan (Jurnal Pustaka Cendekia Pendidikan, 2025)
This paper examines the educational values ​​and character building applied in Imran's family as reflected in the story contained in Surah Ali 'Imran and other narratives in the Qur'an. Through an analysis of the story of Imran's wife's vow, the surrender of Maryam to the Prophet Zakariya, and the instillation of the principle of monotheism from an early age, the article emphasizes that success in building a generation of faith and piety is not only based on internal aspects of the family, but is also greatly influenced by external factors such as a conducive environment, prayer, and sincere intentions from parents. A religious and exemplary environment, as chosen and managed by Imran's family, is an important factor in shaping children's character as a whole by instilling moral, spiritual, and social values ​​according to Islamic principles. In addition, the article highlights that Imran's family education emphasizes the importance of consistency, sincerity, and prayer in the process of educating children so that they grow into individuals who are not only intellectually intelligent, but also strong in faith and noble morals. Thus, Imran's family is an ideal model that is able to integrate spiritual and moral aspects as the main foundation in building a future generation that is faithful and pious according to Islamic teachings.